Pengaruh Love Of Money dan Self Assessment System Terhadap Tax Evasion: Peran Moderasi Akhlak - Nurdalila Ashilah Ubaid; Lince Bulutoding; Della Fadhilatunisa (Academic Bright Collaboration, 2025)
This study aims to examine the influence of love of money and the self assessment system on tax evasion, with morality as a moderating variable. The research adopts a quantitative approach using a causal comparative method. The sample consisted of 100 respondents, namely muslim individual taxpayers registered at KP2KP Sungguminasa, selected through purposive sampling techniques. Data were collected using questionnaires and analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with an absolute difference approach. The results indicate that love of money has a significant positive effect on tax evasion, with a p-value of 0.001. similarly, the self assessment system also shows a significant positive effect on tax evasion, with a p-value of 0.003. Meanwhile, morality does not moderate the relationship between love of money and tax evasion (p= 0.080), but it does moderate the relationship between the self assessment system and tax evasion, with a p-value of 0.015. The implications of this study underline the importance of moral formation in improving tax compliance, so that efforts to prevent tax evasion can be carried out more effectively.